The use of growth hormone-releasing hormone in the diagnosis and treatment of short stature. - Grossman, A; Savage, M; Blacklay, A; Ross, R; Plowman, P; Preece, M; Coy, D; Besser, G (1985)
We have assessed the role of growth hormone-releasing hormone (GHRH) as a diagnostic test in 40 children and young adults with growth hormone deficiency (GHD), principally using the GHRH(1-29)NH2 analogue. Following 200 micrograms GHRH as an acute intravenous bolus, serum GH rose to normal or just subnormal levels in 13 out of 17 children with structural lesions, and in 8 of 14 patients with idiopathic GHD or panhypopituitarism. Of 9 children (mean age 12 years) with GHD following treatment with cranial irradiation for nonendocrine tumours, all responded acutely to GHRH. 12- and 24-hour infusions with GHRH(1-29)NH2, and 1- and 2-week treatments with twice-daily subcutaneous GHRH(1-29)NH2, showed persistent stimulation of GH release. It is concluded that many children with GHD of diverse aetiology will respond both acutely and chronically to treatment with GHRH.